Intra‐fractional motion error during HyperArc stereotactic radiosurgery on patients with brain metastases: Comparison of open and full‐face clamshell‐style immobilization devices. Issue 4 (20th January 2022) - Ohira, Shingo; Komiyama, Riho; Kanayama, Naoyuki; Ueda, Yoshihiro; Inui, Shoki; Miyazaki, Masayoshi; Koizumi, Masahiko; Konishi, Koji
Abstract: Purpose: To compare the intrafractional motion error (IME) during stereotactic irradiation (STI) in patients with brain metastases immobilized using open‐ (Encompass) and full‐face (DSPS) clamshell‐style immobilization devices. Methods: Encompass (38 patients) and DSPS (38 patients) were used for patient immobilization, and HyperArc plans with three to four non‐coplanar beams were generated to deliver 25 to 35 Gy in three to five fractions. Cone‐beam computed tomography (CBCT) was performed on patients before and after the treatment. Moreover, the difference in patient position between the two CBCT images was considered as the IME. The margins to compensate for IME were calculated using the van Herk margin formula. Results: For Encompass, the mean values of IME in the translational setup were 0.1, 0.2, and 0.0 mm in the anterior–posterior, superior–inferior, and left–right directions, respectively, and the mean values of IME about rotational axes were −0.1, 0.0, and 0.0° for the Pitch, Roll, and Yaw rotations, respectively. For DSPS, the mean values of IME in the translational setup were 0.2, 0.2, and 0.0 mm in the anterior–posterior, superior–inferior, and left–right directions, respectively, and the mean values of IME about rotational axes were −0.1, −0.1, and 0.0° for the Pitch, Roll, and Yaw rotations, respectively. No statistically significant difference was observed between the IME of the two immobilization systems except in the anterior–posterior direction ( p  = 0.02). Moreover, no statistically significant correlation was observed between three‐dimensional IME and treatment time. The margin compensation for IME was less than 1 mm for both immobilization devices. Conclusions: The IME during STI using open‐ and full‐face clamshell‐style immobilization devices is approximately equal considering the adequate accuracy in patient positioning.